X-ray study of the precipitation of hydrogen in vanadium - Bonfiglioli, A.; Batterman, B. W. (Comisión Nacional de Energía Atómica; Argentina, 1969)
Fil: Bonfiglioli, A. Comisión Nacional de Energía Atómica; Argentina